Prevalence of Sarcopenia in Patients With COVID-19: A Systematic Review and Meta-Analysis - Xu, Ying; Xu, Jia-wen; You, Peng; Wang, Bing-Long; Liu, Chao; Chien, Ching-Wen; Tung, Tao-Hsin (Frontiers in Nutrition, 2022)
Background: It has been speculated that patients with sarcopenia are aggravated by the current 2019 novel coronavirus disease (COVID-19) epidemic. However, there is substantial uncertainty regarding the prevalence of sarcopenia in COVID-19 patients. Objectives: To systematically evaluate the prevalence of sarcopenia in COVID-19 patients, including stratification by gender, study location, study population, study design, and diagnostic criteria. Methods: Four main electronic databases were searched to identify observational studies reporting a prevalence estimate for sarcopenia in COVID-19 patients. Studies were reviewed in accordance with the Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) guidelines and a meta-analysis was performed. Risk of bias (RoB) was assessed using the Newcastle-Ottawa Scale (NOS), and Stata 14.0 was used to perform meta-analyses. Results: 2,721 studies were initially identified. After removing the duplicates and applying the selection criteria, we reviewed 91 full-text studies. A total of 8 studies, including 1,221 patients, were eligible for inclusion in this review finally. The prevalence of sarcopenia in COVID-19 patients in individual studies varied from 23.97% to 90.21%. The pooled prevalence of sarcopenia in COVID-19 was 58.8% (95% confidence interval, CI: 39.1% to 78.6%, I2 = 98.679%, P < 0.0001). We did not find any significant differences in the prevalence estimates between gender specificity (RR = 0.96; 95% CI = 0.71–1.29; p = 0.526). By sex, the prevalence was 38.7% (95% CI: 22.0-55.4%) in males and 29.2% (95% CI: 22.5-35.9%) in females. The prevalence estimates significantly varied based on population settings and screening tools. ICU patients (74.9%, 95% CI: 58.4-91.4%) were more likely to suffer from sarcopenia compared to other population settings. Conclusion: To our knowledge, this is the first meta-analysis reporting on the prevalence of sarcopenia in COVID-19 patients. Sarcopenia is frequently observed in COVID-19 patients, with varying prevalence across population settings. This study would be useful for clinicians to prompt the increasing awareness of identifying sarcopenia and developing interventions at COVID-19 patients with high risk of sarcopenia. Further prospective longitudinal studies to define the association of sarcopenia and its prognostic outcomes in COVID-19 survivors are needed to propose the most appropriate treatment strategies during admission and discharge.